Pedoman Hamba Tuhan Dan Pemimpin Berdasarkan 1 Petrus 5:3,6 - Suarman Menzuari Waruwu; Abad Jaya Zega (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
This research discusses the role and leadership characteristics of a Servant of God in the Christian context, especially in the church environment. Leadership of God's Servants is analyzed through the concepts of service leadership, spiritual mindset, and example. The research method used is a qualitative study which reflects the reality faced by a Servant of God in his ministry. The research results show that the leadership of God's Servants includes aspects of service that are based on the service model of Jesus Christ. Christian leaders are expected to have the qualities of humility, service, and selflessness. Leadership of God's Servants also requires a spiritual mindset that involves insight, wisdom, and commitment to God's Word. Apart from that, the leader's example is an important key in shaping the character of the congregation and having a positive impact on the surrounding environment.